The influence of project-based mathematics learning on 21st century skills (4C's) considering students' learning styles and teachers' instructional methods - Dwi Yulianto; Moh. Rizal Umami; Syahrul Anwar; Egi Adha Juniawan; Yusup Junaedi (State Islamic University of North Sumatra, 2024)
This study aims to evaluate the impact of project-based learning (PjBL) in mathematics on the development of 21st-century skills, including critical thinking, communication, collaboration, and creativity. These skills are essential for preparing students to face the challenges of the modern era. However, traditional teaching methods often prove inadequate for optimizing these skills. Utilizing a 3×4 quasi-experimental factorial design, this study involved 90 students, proportionally selected from a population of 872 through random sampling. Data were collected using a learning style questionnaire, observations of teacher instructional methods, and a written test to measure 21st-century skills. Data were analyzed using tests for normality and two-way ANOVA. The results demonstrated that the PjBL approach significantly enhanced students' 21st-century skills (4Cs: Critical Thinking, Collaboration, Communication, Creativity), particularly for those with a kinesthetic learning style and when employing technology-based teaching methods. The interaction between PjBL, students' learning styles, and teachers' instructional methods was found to be effective in fostering the development of these skills, especially in the areas of creativity and problem-solving. This research underscores the importance of innovative approaches in mathematics education to support the development of 21st-century skills.